Proof of The Formation of OH Radicals from Methyl Paraben and Its Effect on Cancer Formation - Rizkita, Aden Dhana; Pamungkas, Wilis Okti; Dewi, Sintia Ayu; Angganawati, Rahmadhani Tyas; Rochjana, Anna Uswatun Hasanah; Firmansyah, Azhari; Saputra, Reza Pratama (Proceeding International Conference on Religion, Science and Education, 2022)
Methyl paraben is often used by the cosmetic industry such as facial moisturizer, anti-aging, hair dye, skin whitening, shaving gel, eye shadow and others because it is considered non-toxic. However, in fact, several studies have found that methyl paraben is able to accumulate in the body, resulting in the formation of radicals. Because of its ability to produce radicals, this paper tries to prove that methyl paraben used in the cosmetic industry must be considered immediately. Because we suspect that exposure to radicals from methyl paraben will be able to interact with DNA, causing DNA mutations that lead to cancer. In this summary, we prove that exposure to methyl paraben in mice is able to produce DNA mutation biomarker products with the formation of 8-Hydroxy-2’-Deoxyguanosine (8-OHdG), either by direct metabolism or by oxidative stress triggered by the presence of metal ions in the Fenton reaction such as Cu and Fe. The method used is direct in-vivo exposure to test animals and in-vitro to prove it by synthesizing the DNA damage biomarker product using LCMS.